Capped steam ahead: A case study among ship operators on a maritime ETS - Simon Koesler; Martin Achtnicht; Jonathan Köhler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
International shipping is an important emitter of greenhouse gases. The International Maritime Organization (IMO) is discussing different approaches to reduce maritime CO2 emissions, in particular market-based mechanisms. In this paper, we assess potential implications of a maritime emission trading scheme (ETS) on the organisation and operations of shipping companies, primarily on the basis of a case study involving ship operators. Our results suggest that there is no knock-out criterion why a cap-andtrade approach should not work in the shipping sector in practice. A maritime ETS has the potential to engage this sector into cost-efficient emission reduction if designed to account for the special characteristics of the international shipping industry.
Keywords: L91; Q54; Q58; R48; 330; emission trading; international shipping; maritime emissions